2020
DOI: 10.1186/s12887-020-02179-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital malformations at the “les Orangers” maternity and reproductive health Hospital of Rabat: descriptive study of 470 anomalies

Abstract: Background: Congenital malformations are described in about 3% of live births and 20% of stillbirths in the industrialized countries. The prevalence of congenital anomalies in developing countries, including Morocco, is not well known at the national level. The aim of our study is to conduct a descriptive exploratory analysis of congenital malformations cases diagnosed at the "Les Orangers" Maternity and Reproductive Health Hospital in Rabat. Methods: We collected all the cases of congenital malformations diag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…In this systematic review and meta-analysis, 60 articles, which included about 3,091,946 births and 52,569 congenital anomalies, were analyzed. Of these, 4 studies were conducted in Ethiopia [ 30 – 33 ]; 16 studies were conducted in Nigeria [ 34 48 ]; 9 studies were conducted in Egypt [ 49 59 ]; 3 studies were conducted in South Africa [ 60 – 64 ]; 5 studies were conducted in Morocco [ 65 69 ]; 6 studies were conducted in Libya [ 70 – 75 ]; 2 studies were conducted in Tunisia [ 76 79 ]; and 7 studies were conducted in Mozambique [ 80 ], Botswana [ 81 ], Cameroon [ 82 ], the DRC [ 83 ], Malawi [ 84 ], Zambia [ 85 ], Gabon [ 86 ], and Uganda [ 87 ]. Two studies were from Sudan [ 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this systematic review and meta-analysis, 60 articles, which included about 3,091,946 births and 52,569 congenital anomalies, were analyzed. Of these, 4 studies were conducted in Ethiopia [ 30 – 33 ]; 16 studies were conducted in Nigeria [ 34 48 ]; 9 studies were conducted in Egypt [ 49 59 ]; 3 studies were conducted in South Africa [ 60 – 64 ]; 5 studies were conducted in Morocco [ 65 69 ]; 6 studies were conducted in Libya [ 70 – 75 ]; 2 studies were conducted in Tunisia [ 76 79 ]; and 7 studies were conducted in Mozambique [ 80 ], Botswana [ 81 ], Cameroon [ 82 ], the DRC [ 83 ], Malawi [ 84 ], Zambia [ 85 ], Gabon [ 86 ], and Uganda [ 87 ]. Two studies were from Sudan [ 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review and meta-analysis, 60 articles, which included about 3,091,946 births and 52,569 congenital anomalies, were analyzed. Of these, 4 studies were conducted in Ethiopia [30][31][32][33]; 16 studies were conducted in Nigeria [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; 9 studies were conducted in Egypt [49][50][51][52][53][54][55][56][57][58][59]; 3 studies were conducted in South Africa [60][61][62][63][64]; 5 studies were conducted in Morocco [65][66][67][68][69]; 6 studies were conducted in Libya [70][71][72][73][74][75]; 2 studies were conducted in Tunisia [76][77]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Антенатальну діагностику природжених вад розвитку проведено у 28,6 % випадків, решту діагностовано після пологів, із них 19,2 % становили мертвонародження [11], що свідчить про недоступність пренатальної діагностики для багатьох верств населення країн, що розвиваються, на відміну від України та інших країн Європи.…”
Section: оригінальні дослідженняunclassified
“…Laparoschisis 1 is 'a congenital malformation characterized by the absence of the abdominal covering sac and/or sub-cutaneous and cutaneous tissues, exposing viscera to the external environment'. Previous research [1][2][3][4][5][6][7] reported a moderate prevalence of 1 per 6,000 births in Europe and 4.4 per 10,000 births in Canada, While the disease has not been extensively studied in Africa, results from facility-based studies [8][9][10] suggest that laparoschisis represents between 5-12% of total congenital malformations diagnosed in West and Northern Africa. The authors'article1 also reported that it occurs around teen weeks of gestational age and results in bowel protruding without covering sac, adding that antenatal diagnosis is rare due to the lack of antenatal optimal investigation, mainly ultrasound in rural health care facilities.…”
Section: Introductionmentioning
confidence: 99%